ПУТИ РАЗВИТИЯ ЗАПАДНОГО ПЕРЕВОДОВЕДЕНИЯ От языковой асимметрии к политической - Prunc, Erich (R. Valent, 2015)
The development of translation studies is outlined against the epistemological and intellectual background that characterized the rise of the new discipline and which has to be taken into account if one is to understand the history and the present state of translation studies as a special research field. The monograph offers a detailed and convincing explanation of the ways in which single theories of translation evolved, showing what are the points that they have in common and how they differ from one another in their aims and methods. The theoretical approaches to translation that arose in the German-speaking academic environments (especially H. Vermeer's and K. Reiss's Skopostheorie, J. Holz-Mänttari's Theorie vom translatorischen Handeln and Ch. Nord's approach with »loyalty« as a central cencept) are also presented in comparison to other schools of translation research which developed elsewhere in Europe and beyond.